Ischemic preconditioning slightly enhances Jiu Jitsu performance - Santos, I. A.; Corrêa da Silva, B. V.; Xavier de Oliveira, D. C.; Carvalho da Cruz, G. G.; Puggina, E. F.; Mota, G. R. (International Journal of Sports Medicine, 2026)
This study aimed to determine whether acute ischemic preconditioning enhances performance in the Jiu-Jitsu anaerobic performance test and its influence on physiological responses in Brazilian Jiu-Jitsu fighters. Seventeen male fighters completed two randomized crossover sessions (ischemic preconditioning and placebo). The ischemic preconditioning protocol consisted of three cycles of 5-minute occlusion at 220 mm Hg followed by 5-minute reperfusion. Performance was assessed using the Jiu-Jitsu anaerobic performance test, while physiological markers included the heart rate, blood lactate, muscle oxygenation, countermovement jump, rating of perceived exertion, and session rating of perceived exertion. Ischemic preconditioning increased total repetitions performed in the Jiu-Jitsu anaerobic performance test (p=0.003) and enhanced muscle oxygenation (p<0.0001). Under the placebo condition, the pre-countermovement jump was higher than the post-countermovement jump (p=0.006). However, under the ischemic preconditioning condition, no significant difference was observed between pre- and post-countermovement jump (p=0.99). No significant differences were observed for heart rate or blood lactate (p>0.05). Additionally, ischemic preconditioning reduced the session rating of perceived exertion compared to the placebo (p=0.04), suggesting a lower session rating of perceived exertion. We concluded that acute ischemic preconditioning induces small but significant improvements in performance and muscle oxygenation, while reducing fatigue and session rating of perceived exertion in Brazilian Jiu-Jitsu athletes, supporting its use as an ergogenic aid in training.